Trend Significance Levels of Rain Onset and Cessation and Lengths of the Wet and Dry Seasons in Epe, Lagos State, Nigeria - Alli, Adekunle Adedeji; Omofunmi, Olorunwa Eric (UI Scholars Hub, 2021)
This study aims to reduce crop failure resulting from a dry spell, which is the first occurrence of unsustainable rainfall that deceives farmers into planting. Thus, trends need to be tested using hypothesis, kurtosis, and other statistics to analyze the risks associated with unstable planting calendars and their possible mitigation strategies. The daily rainfall data from 1982 to 2018 were obtained from the archive of NASA/POWER SRB/FLASH, and the research location is Epe, Lagos State, Nigeria, which lies at latitude 6.585° N and longitude 3.962° E. Microsoft Excel was used to perform the tests. Results show that the null hypothesis of no trend in the distribution was rejected on the basis of the fact that the probability value (p = 0.00) is less than the significance level (α = 0.05). The mean onset and cessation dates are March 27 and October 18, with skewness values of −0.63 and 11.02, respectively. Rain onset and cessation that occur from February 12 to April 27 and from September 28 to November 28, respectively, are safe with low risks of dry spell. Moreover, drought and dry spell were most probable in years that experienced a shorter length of wet season than dry season.